2009
DOI: 10.1245/s10434-009-0616-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Positive Surgical Margin Status on Gastric Cancer Patients Undergoing Gastrectomy

Abstract: Aggressive tumor biology might be the main factor contributing to positive microscopic resection margin after gastrectomy. Positive resection margin had a definite unfavorable impact on the OS of gastric cancer patients undergoing gastrectomy. When GC patients underwent gastrectomy with positive resection margin, positive nodal metastasis determined the worst OS, and distant metastasis was the most common site of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
96
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 8 publications
13
96
0
Order By: Relevance
“…The prognostic impact of this RM involvement by the tumor has been widely studied by several authors: in a multicenter Italian study, Morgagni et al [4] showed that RM infiltration is an independent unfavorable factor in patients who underwent gastrectomy (OR 1.5), with a 5-year OS rate of 66 % in R0 resections and 29 % in R1 resections. Eastern authors [3,5,14,15] observed similar results, with an unstratified 5-year survival rate ranging from 53 to 60 % in the case of R0 resections, and from 13 to 26 % in case of R1 resections. In the present study we found that the 5-year survival rate of the whole cohort was 59 % in patients with negative RMs and 22 % in patients with positive RMs; therefore, the data we are presenting perfectly overlap with those reported in the literature.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…The prognostic impact of this RM involvement by the tumor has been widely studied by several authors: in a multicenter Italian study, Morgagni et al [4] showed that RM infiltration is an independent unfavorable factor in patients who underwent gastrectomy (OR 1.5), with a 5-year OS rate of 66 % in R0 resections and 29 % in R1 resections. Eastern authors [3,5,14,15] observed similar results, with an unstratified 5-year survival rate ranging from 53 to 60 % in the case of R0 resections, and from 13 to 26 % in case of R1 resections. In the present study we found that the 5-year survival rate of the whole cohort was 59 % in patients with negative RMs and 22 % in patients with positive RMs; therefore, the data we are presenting perfectly overlap with those reported in the literature.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, Morgagni [1] and Nakamura et al [19] showed that the prognosis of patients with EGC is not affected by the presence of positive RMs, because of the excellent survival for this type of disease. Finally, in contrast to the above results, Wang et al [14] found that positive margins affect survival despite the tumor category.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Multiple studies have demonstrated that microscopically positive (R1) margins after resection can be associated with worse prognosis, although the prognostic effect can differ between early-and advanced-stage gc [25][26][27][28][29][30][31] . On multivariate analysis, the predictors for a positive margin include higher T stage, higher N stage, larger tumour size, and diffuse histologic type 24,[28][29][30] . Use of ifs of the resection lines is common for the assessment of margin status.…”
Section: Summary Of Evidencementioning
confidence: 99%